APPLICATION OF TRADITIONAL MEDICINE AS A COMPANION TO MEDICAL TREATMENT - Nooraisyah Nooraisyah; Nur Aini Bunyani; Charisal Matsen A Manu (Adisam Publisher, 2025)
This paper aims to examine the application of traditional medicine as a complement to medical treatment, focusing on its benefits, constraints and powerful integration strategies. Indigenous medicine has long been applied in various cultures to manage health and disease, and is increasingly accepted as a complement to contemporary medical treatment in the pursuit of whole health care. The research method included a literature review. The results showed that traditional medicine can have significant benefits in alleviating certain symptoms, improving patients' quality of life, and offering a more personalized approach that is in line with individual cultural values. Patients who combine traditional medicine with medical treatment often report improved inner and outer well-being. However, this study also found several barriers, including differences in scientific methods and validation, inadequate regulation, and a lack of formal training for traditional medicine practitioners. These barriers often stand in the way of effective and safe integration.